2020
DOI: 10.1002/acn3.51046
|View full text |Cite
|
Sign up to set email alerts
|

Genetic modifiers of respiratory function in Duchenne muscular dystrophy

Abstract: Objective: Respiratory insufficiency is a major complication of Duchenne muscular dystrophy (DMD). Its progression shows considerable interindividual variability, which has been less thoroughly characterized and understood than in skeletal muscle. We collected pulmonary function testing (PFT) data from a large retrospective cohort followed at Centers collaborating in the Italian DMD Network. Furthermore, we analyzed PFT associations with different DMD mutation types, and with genetic variants in SPP1, LTBP4, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 36 publications
(69 citation statements)
references
References 40 publications
1
62
0
Order By: Relevance
“…Glucocorticoid (GC) therapy is currently standard of care in DMD as multiple studies have shown this therapy helps slows the progressive decline in skeletal muscle and pulmonary function 15,19 20,21 …”
Section: Glucocorticoid Treatmentmentioning
confidence: 99%
“…Glucocorticoid (GC) therapy is currently standard of care in DMD as multiple studies have shown this therapy helps slows the progressive decline in skeletal muscle and pulmonary function 15,19 20,21 …”
Section: Glucocorticoid Treatmentmentioning
confidence: 99%
“…There are numerous candidates for modifiers of the dystrophin gene and the latest candidates have been described in various publications 29,31,32 . Most of the studies describe how modifiers affect skeletal muscle, with a few reports focusing on modifiers of pulmonary and cardiac function 32‐34 . While there is an association between pulmonary phenotype and age at loss of ambulation (e.g., patients with the most severe pulmonary phenotype experience loss of ambulation at the earliest age), 14 the relationship between skeletal muscle deterioration and cardiopulmonary phenotypes is not well‐studied.…”
Section: Personalized Patient Prognosis and Strategies For New Therapiesmentioning
confidence: 99%
“…An enduring challenge even in a monogenic disease such as DMD is disease heterogeneity, and variability in clinical outcomes is evident across multiple organs 4‐16 . Both DMD genotype and genetic modifiers affect motor, respiratory, and cognitive outcomes in DMD.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, boys with distal DMD pathogenic variants were shown to have lower pulmonary function measures compared to those with proximal DMD pathogenic variants 5 . Similarly, cognitive burden in DMD vary depending between boys with proximal and distal DMD pathogenic variants 14‐18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation